Volunteens a study on how leaders of youth volunteer organizations communicate volunteerism and how it is perceived by the members - Balinguit, Erika Damalerio 1992- (2012)
"This study looked into how leaders of youth volunteer organizations (YVOs) communicate volunteerism among their members. Specifically, the study examined the identities, values, motivation and roles, and communication and leadership styles of the YVO leaders. It also ascertained the influences of these identities and styles on the members' values, motivations, views of the organization, participation in its activities and relationships within the organization. Michael Hecht's Communication Theory of Identity (CTI) and Robert House's Path-Goal Theory was used in order to explain the leaders' identities and styles and its influence on members. Surveys and interviews were utilized in order to gather the data. Results showed that leaders in youth volunteer organizations are dramatic, precise and attentive communicators. They also frequently apply participative and achievement-oriented communicators. They also frequently apply participative and achievement-oriented leadership style. These approaches effectively influence the members to volunteer and participate in the organization."